(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
The study was conducted to evaluate 17 tomato cultivars for higher postharvest quality and shelf life under storage conditions during the summer season in Bangladesh at the Postharvest Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from May 2025 to July 2025, with the objective of identifying suitable cultivars for storage, transportation, and marketing in the summer season. Postharvest quality parameters were assessed and significant variation was observed among cultivars. In regard to postharvest behavior of tomato, Maximum TSS (9.1%) and pH (4.87) were exhibited by Raja Super and Udayan, respectively. Whereas maximum weight loss (10.91%) and firmness (2.10 kg cm-2) were exhibited by Binatomato-13 and Raja Super, respectively, at 10 days of storage. Maximum dry matter content (9.54%) exhibited by Deshi pathorkuchi and conversely, maximum moisture content (95.23%) identified in Binatomato-7. Jholmol recorded the highest disease incidence (60%) and severity (55.47%) after 10 days of storage, while Ratan, Raja Super, Rubi, Udayan, Unnayan, and Chakra showed no disease incidence or severity during the storage period. And finally, the longest shelf life (15.17 days) was observed from Chakra, followed by Udayan (15.13 days), Le16 (Deshi patharkuchi) (14.83 days) and Le7 (Raja Super) (14.33 days). Hence, the findings highlight the potential of cultivars such as Chakra, Udayan, and Raja Super for commercial cultivation and long-term storage and transportation during the summer season in Bangladesh. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 333-352.